Heteronuclear composite zinc negative electrode material based on in-situ construction of zeolite imidazate skeleton, and preparation method and application thereof

By constructing the zeolite imidazolate framework interface layer in situ on the surface of the zinc-based material, the problems such as dendrite growth and corrosion during the cycling process of the zinc-based battery are solved, the electrochemical performance is significantly improved, and high stability and low interface are achieved. resistance.

CN119361632APending Publication Date: 2025-01-24SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411454358.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the circulation process, zinc-based batteries have side reactions such as dendrite growth, zinc electrode deformation, hydrogen evolution corrosion and electrolyte consumption, resulting in short cycle life, low Coulomb efficiency, and serious capacity attenuation, which hinders the development and application of zinc-based batteries.

Method used

By building a variety of transition metals as the centered icolizole osteopsis osteoplate interface on the surface of zinc -based material to form a crystalline porous material to improve the interface compatibility and electrochemical stability, and accelerate the de -solvents of zinc ions through nano channels to accelerate the zinc ion. Transfer and uniform transmission, regulate the sedimentary dynamics of zinc ions.

Benefits of technology

The electrochemical performance of zinc-based batteries is significantly improved, achieving high stability, low interface resistance and high cycle stability, meeting the performance requirements of low cost, high safety, high energy and fast response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361632A_ABST
    Figure CN119361632A_ABST
Patent Text Reader

Abstract

The invention relates to a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazate skeleton, and a preparation method and application thereof. The composite zinc negative electrode material takes a zinc-based material as a carrier, and a zeolite imidazate skeleton interface layer taking various different transition metals as centers is constructed on the surface in situ. The zeolite imidazate framework interface layer is formed by mutually connecting a plurality of different transition metals and organic ligands through self-assembly, the transition metals are taken as the center, the organic ligands and the transition metals are bridged, and the zeolite imidazate framework interface layer is made of a crystalline porous material. And immersing the zinc-based material into a mixed solution of the transition metal salt solution and the organic ligand solution, oscillating, washing and drying to obtain the composite zinc negative electrode material. Compared with the prior art, the preparation method has the advantages of good interface compatibility, good electrochemical stability, excellent electrochemical performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage devices, and in particular to a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate skeleton, and a preparation method and application thereof. Background Art

[0002] With the global environmental degradation and the depletion of non-renewable energy reserves, the large-scale application of renewable energy has become an inevitable trend. However, these renewable energy sources are characterized by intermittency and instability. When the proportion of intermittent renewable energy is as high as 25-50%, its fluctuation will have a serious impact on the stability of the power grid. In the face of this challenge, the development of sustainable and low-pollution energy storage technology will serve as the core to support the development of the energy system, and will be used to reduce peak loads and valley loads and mitigate power grid fluctuations. Among the many energy storage technologies, electrochemical energy storage has the advantages of high energy density, long duration, high power, no geographical restrictions, and flexible configuration according to different application requirements.

[0003] At present, electrochemical energy storage devices represented by lithium-ion batteries have the advantages of high specific energy, high operating voltage, high specific power, low self-discharge, and good cycle stability, and they dominate the energy storage market. However, the flammable organic electrolytes used in commercial lithium batteries are easy to catch fire or even explode, posing huge safety hazards. In addition, the economic cost of lithium-ion batteries is relatively high, and the battery assembly is also complicated. Moreover, a large amount of discarded lithium-containing organic electrolytes and heavy metal ions also pose another major environmental problem. Compared with lithium-ion batteries based on organic electrolytes, zinc-based batteries using aqueous electrolytes have the following advantages: 1) low cost; 2) environmental friendliness, because aqueous electrolytes are non-toxic and non-flammable; 3) high ionic conductivity, so that the battery has the ability of fast charging and high power density; 4) high safety. In addition, water, as an ideal electrolyte solvent, has great advantages in recycling discarded aqueous batteries. Therefore, from the perspectives of safety, economy, and ecology, zinc-based batteries have great potential in large-scale energy storage applications.

[0004] However, since aqueous electrolytes can cause a series of side reactions, including dendrite growth of the zinc negative electrode during the cycle, deformation of the zinc electrode, hydrogen evolution corrosion, and continuous consumption of the electrolyte, the actual performance of zinc-based batteries is unsatisfactory, such as short cycle life, low Coulomb efficiency, and severe capacity decay, which greatly hinders the development and application of zinc-based batteries. In response to the above problems, the current solutions for constructing highly stable zinc negative electrodes mainly include designing multi-scale zinc structures and constructing artificial interface layers. The former can effectively increase the specific surface area to achieve uniform electric field distribution, but will aggravate corrosion and hydrogen evolution; the latter cannot simultaneously meet high zinc ion migration numbers and electrical conductivity.

[0005] Patent publication number CN117691035A discloses a zinc ion battery negative electrode material modulated by in-situ growth of metal-organic framework and its preparation method. The preparation method uses zinc foil as the substrate, dimethyl imidazole and copper nitrate are added to CH3OH and stirred, the solution is mixed and then subjected to hydrothermal reaction, and the product after the reaction is washed and dried to form Cu-MOF deposited on the surface of the zinc foil. However, the chemical and electrochemical compatibility of the negative electrode material is relatively poor, which is not conducive to reducing the side reactions inside the battery, improving the cycle stability and life of the battery, and improving the overall performance of the battery. Summary of the invention

[0006] The purpose of the present invention is to provide a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate skeleton, as well as a preparation method and application in order to overcome the defects of the above-mentioned prior art. A zeolite imidazolate skeleton interface layer with one or more transition metal centers is in-situ constructed on the surface of a zinc-based material. The in-situ construction makes the interface layer have good interface compatibility and electrochemical stability, thereby realizing a highly stable zinc metal negative electrode; and the zeolite imidazolate skeleton has abundant nanochannels, which accelerate the desolvation of zinc ions through confinement, realize uniform transmission of zinc ions, and regulate the deposition kinetics of zinc ions, thereby significantly improving the electrochemical performance of zinc-based batteries.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a heteronuclear composite zinc negative electrode material based on an in-situ constructed zeolite imidazolate skeleton. The composite zinc negative electrode material uses a zinc-based material as a carrier, and an in-situ constructed zeolite imidazolate skeleton interface layer centered on a variety of different transition metals on the surface.

[0009] Furthermore, the zeolite imidazolate skeleton interface layer is formed by a plurality of different transition metals and organic ligands interconnected by self-assembly, wherein the transition metal is the center and the organic ligands are linked to the transition metal. The zeolite imidazolate skeleton interface layer is a crystalline porous material.

[0010] Furthermore, the transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium;

[0011] The organic ligands include 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, and 2-bromobenzimidazole;

[0012] The zinc-based material comprises a zinc foil substrate.

[0013] The second technical solution of the present invention is to provide a method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate skeleton, wherein the zinc-based material is immersed in a mixture of a transition metal salt solution and an organic ligand solution, and after shaking, washing and drying, the composite zinc negative electrode material is obtained.

[0014] Further, the zinc-based material includes a zinc foil substrate;

[0015] The transition metal salt in the transition metal salt solution includes nitrate, acetate or chloride of a transition metal, the transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium, and the solvent includes one or more of water, methanol, ethanol and dimethylformamide;

[0016] The organic ligand of the organic ligand solution includes 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, 2-bromobenzimidazole, and the solvent includes one or more of water, methanol, ethanol, and dimethylformamide.

[0017] Furthermore, the transition metal salt in the transition metal salt solution includes two or more of zinc nitrate, zinc acetate, zinc chloride, manganese nitrate, manganese acetate, manganese chloride, nickel nitrate, nickel acetate, nickel chloride, cobalt nitrate, cobalt acetate, and cobalt chloride.

[0018] Furthermore, the molar ratio of the transition metal salt to the organic ligand is 1:2 to 10;

[0019] The mass concentration of the transition metal salt is 5 to 15 mg / mL;

[0020] The mass concentration of the organic ligand is 4-30 mg / mL.

[0021] Furthermore, the mass concentration of the transition metal salt is 6 to 10 mg / mL;

[0022] The mass concentration of the organic ligand is 8-16 mg / mL.

[0023] Furthermore, the oscillation temperature is room temperature.

[0024] Furthermore, before immersing the zinc-based material in the mixture of the transition metal salt solution and the organic ligand solution, the zinc-based material is pretreated, and the pretreatment process is as follows: the surface of the zinc-based material is polished and cleaned, and then immersed in an etching solution for etching treatment;

[0025] The etching solution includes a mixed solution of sodium hydroxide and ammonium persulfate.

[0026] Furthermore, the zinc-based material is first immersed in the organic ligand solution, oscillated at room temperature for 1 to 5 hours, and then the transition metal salt solution is dripped into the organic ligand solution, oscillated at room temperature for 12 to 48 hours, washed and then dried at 60 to 90° C. to obtain the composite zinc negative electrode material.

[0027] Furthermore, the preparation method of the composite zinc negative electrode material comprises the following steps:

[0028] S1. Grind and clean the surface of the zinc-based material;

[0029] S2, immersing the cleaned zinc substrate in an etching solution for etching;

[0030] S3. Pour the salt solution and the ligand solution into the cleaned zinc-based material in sequence and immerse them, shake at room temperature, wash and dry to obtain the composite zinc negative electrode material.

[0031] The third technical solution of the present invention is to provide an application of a heteronuclear composite zinc negative electrode material based on an in-situ constructed zeolite imidazolate skeleton in the field of electrochemical energy storage devices, characterized in that the electrochemical energy storage device includes a zinc ion battery, a zinc-air battery or a zinc-iodine battery.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The present invention constructs a zeolite imidazolate skeleton interface layer in situ, and compared with the interface layer of other non-in-situ physical coatings, the problem of cracking or detaching from the zinc foil surface will not occur during repeated cycles. The in-situ interface layer can penetrate into the substrate during the formation process, thereby enhancing the mechanical bite of the interface and improving the interface bonding strength. This bonding method is stronger than non-in-situ physical coatings, can more effectively transfer stress, and reduce stress concentration and crack formation at the interface. At the same time, the in-situ interface layer can alleviate the difference in elastic modulus between the coating and the substrate, reduce the bending and deformation of the coating during the stress process, and thus improve the overall mechanical properties of the coating.

[0034] (2) The zeolite imidazolate framework prepared by the present invention has excellent thermal, mechanical and chemical / electrochemical stability, can effectively inhibit dendrite growth, protect the zinc negative electrode from corrosion, reduce the occurrence of side reactions, and form a protective layer with high stability and low interface resistance.

[0035] (3) The present invention achieves uniform interfacial electric field distribution and ion flux, reduces desolvation energy, effectively inhibits dendrite growth, significantly reduces polarization generated at the metal anode / electrolyte interface during the electrochemical process, and constructs a low-energy barrier ion transport channel to simultaneously meet high zinc ion migration numbers and ionic conductivity.

[0036] (4) The in-situ constructed zeolite imidazolate framework composite zinc negative electrode material prepared by the present invention is applied to a high specific energy zinc-based battery system using a high-energy positive electrode, a thin zinc negative electrode (<30um) and a lean solution to meet the performance requirements of low cost, high safety, high energy, and rapid response, especially to improve the comprehensive electrochemical performance of the battery over the entire life cycle under actual operating conditions (such as peak and frequency regulation, dynamic acceleration and regenerative braking processes, operating cycle life, etc.), which is expected to provide a new path for driving high-performance zinc-based batteries and create significant economic, environmental and social benefits.

[0037] (5) The in-situ constructed heteronuclear zeolite imidazolate framework composite zinc negative electrode material prepared by the present invention, compared with the in-situ constructed mononuclear zeolite imidazolate framework composite zinc negative electrode material, the different metal ions in the heteronuclear MOF can provide more active sites, thereby showing higher activity and selectivity in the catalytic reaction. For example, by introducing metal ions with catalytic activity into MOF, it can be used to catalyze various chemical reactions. At the same time, the structure and properties of the heteronuclear MOF can be finely controlled by changing the type and proportion of the transition metal center, thereby improving the electrochemical performance of the composite zinc negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a SEM image of the surface of ZIF-L(Ni)@Zn prepared in Example 1;

[0039] Figure 2 This is a SEM image of the cross section of the ZIF-L(Ni)@Zn prepared in Example 1;

[0040] Figure 3 The surface SEM image of the ex-situ ZIF-8@Zn shown in Comparative Example 2;

[0041] Figure 4 is a cross-sectional SEM image of the ex-situ ZIF-8@Zn shown in Comparative Example 2;

[0042] Figure 5 This is the SEM image of the surface of ZIF-8@Zn prepared in Comparative Example 5;

[0043] Figure 6 This is a SEM image of the cross section of ZIF-8@Zn prepared in Comparative Example 5;

[0044] Figure 7 Attached diagram is the contact angle of ZIF-L(Ni)@Zn obtained in Example 1 and Comparative Example 3, ex-situ ZIF-L(Ni)@Zn and bare zinc negative electrode material of Comparative Example 1;

[0045] Figure 8The ZIF-L(Ni)@Zn of Example 1 and the ex-situ ZIF-L(Ni)@Zn of Comparative Example 3 were used as negative electrode materials for zinc ion full batteries at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under current density

[0046] Fig. 9 The ZIF-8@Zn prepared in comparative example 5 and the bare zinc negative electrode material prepared in comparative example 1 were used as negative electrode materials for zinc-iodine batteries at 1A g -1 Comparison of cycling stability under different current densities;

[0047] Fig.10 The ZIF-8@Zn prepared in comparative example 5 and the ex-situ ZIF-8@Zn prepared in comparative example 2 were assembled into a zinc ion half-cell at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under different current densities;

[0048] Fig.11 The ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 were used as negative electrode materials for zinc ion half-cells at 1 mA cm -2 Comparison of cycling stability under different current densities;

[0049] Fig.12 A comparison chart of the rate performance of ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 as negative electrode materials for zinc ion full batteries at different current densities;

[0050] Fig.13 The ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 were used as negative electrode materials for zinc ion full batteries at 1A g -1 Comparison of cycling stability under different current densities;

[0051] Fig.14 The heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 were used as negative electrode materials for zinc ion half-cells at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under different current densities;

[0052] Fig.15 A comparison chart of the rate performance of the heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 as negative electrode materials for zinc ion full batteries at different current densities;

[0053] Fig.16A comparison chart of the cycling stability of the heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 as negative electrode materials for zinc ion full batteries at a current density of 1A g-1;

[0054] Fig.17 The heteronuclear trimetallic ZIF-8(Mn,Co)@Zn prepared in Example 2 and the mononuclear ZIF-8@Zn prepared in Comparative Example 5 were used as negative electrode materials for zinc ion full battery at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under different current densities. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0056] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.

[0057] In the following embodiments, the zinc foil was purchased from Shenzhen Kejing Zhida Technology Co., Ltd., code: BM.0303001501, MB.0303002201; the kapton tape was purchased from Suzhou Simiyang Electronic Materials Co., Ltd.; the conductive carbon black was purchased from Dongguan Kelude Experimental Equipment Technology Co., Ltd., product model: MA-EN-CO-0005, width 5 cm.

[0058] The CAS number of sodium hydroxide is 1310-73-2, with a purity of 96%, purchased from General; the CAS number of ammonium persulfate is 7727-54-0, with a purity of 99.99%, purchased from Admas; the CAS number of 2-methylimidazole is 693-98-1, with a purity of 98%, purchased from Admas; the CAS number of zinc acetate dihydrate is 5970-45-6, with a purity of 99%, purchased from General; the CAS number of nickel acetate tetrahydrate is 6018-89-9, Purity 98+%, purchased from Admas; Manganese acetate tetrahydrate CAS number: 6156-78-1, purity 98+%, purchased from Admas; Cobalt acetate tetrahydrate CAS number: 6147-53-1, purity 99+%, purchased from Admas; Zinc nitrate hexahydrate CAS number: 10196-18-6, purity 99%, purchased from General; Nickel nitrate hexahydrate CAS number: 13478-00-7, purity 99%, purchased from Admas.

[0059] Manganese dioxide was prepared in the laboratory. The preparation process is referred to "Functional Aerogel Driven Synchronous Modulation of Zn 2+ Interfacial Migration Behavior and ElectrolyteMicroenvironment Enables Highly Reversible Zn Anodes”.

[0060] Zinc iodide was prepared in the laboratory, and the preparation process was referred to as “Marangoni-Driven Self-AssemblyMXene As Functional Membrane Enables Dendrite-Free and Flexible Zinc–IodinePouch Cells”.

[0061] In the following embodiments, the test methods used are as follows:

[0062] Field emission scanning electron microscope (SEM) test, using JSM-7800F equipment model. The amphiphilic double-layer graphene-based composite material was adhered to the conductive glue, and then gold was sprayed for 15s to improve the conductivity of the material, and its surface morphology was observed.

[0063] Electrochemical testing:

[0064] Constant current charge and discharge method (GC): Constant current charge and discharge method is an important method for studying electrochemical properties. Its working principle is mainly to check the charging and discharging process of various electrodes under constant current conditions, record the changes of different power levels of electrodes over time, and determine a series of parameters such as specific capacity, coulomb efficiency, energy efficiency, etc. by analyzing and studying the charging and discharging characteristics of various electrodes, so as to judge the electrochemical performance of materials. The constant current charge and discharge test was carried out using Wuhan Blue Electric CT2001A battery test system.

[0065] A heteronuclear composite zinc negative electrode material based on an in-situ constructed zeolite imidazolate skeleton. The composite zinc negative electrode material uses a zinc-based material as a carrier, and an in-situ constructed zeolite imidazolate skeleton interface layer with multiple different transition metals as the center on the surface.

[0066] As one of the preferred embodiments, the zeolite imidazolate skeleton interface layer is formed by a plurality of different transition metals and organic ligands interconnected by self-assembly, the transition metal is the center, the organic ligands are linked to the transition metal, and the zeolite imidazolate skeleton interface layer is a crystalline porous material.

[0067] As one of the preferred embodiments, the transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium;

[0068] The organic ligands include 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, and 2-bromobenzimidazole;

[0069] The zinc-based material comprises a zinc foil substrate.

[0070] A method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework comprises immersing a zinc-based material in a mixture of a transition metal salt solution and an organic ligand solution, and obtaining the composite zinc negative electrode material after oscillation, washing and drying.

[0071] As one of the preferred embodiments, the zinc-based material includes a zinc foil substrate;

[0072] The transition metal salt in the transition metal salt solution includes nitrate, acetate or chloride of a transition metal, the transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium, and the solvent includes one or more of water, methanol, ethanol and dimethylformamide;

[0073] The organic ligand of the organic ligand solution includes 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, 2-bromobenzimidazole, and the solvent includes one or more of water, methanol, ethanol, and dimethylformamide.

[0074] As one of the preferred embodiments, the transition metal salt in the transition metal salt solution includes two or more of zinc nitrate, zinc acetate, zinc chloride, manganese nitrate, manganese acetate, manganese chloride, nickel nitrate, nickel acetate, nickel chloride, cobalt nitrate, cobalt acetate, and cobalt chloride.

[0075] As one of the preferred embodiments, the molar ratio of the transition metal salt to the organic ligand is 1:2 to 10;

[0076] The mass concentration of the transition metal salt is 5 to 15 mg / mL;

[0077] The mass concentration of the organic ligand is 4-30 mg / mL.

[0078] As one of the preferred embodiments, the mass concentration of the transition metal salt is 6 to 10 mg / mL;

[0079] The mass concentration of the organic ligand is 8-16 mg / mL.

[0080] As one of the preferred implementations, the oscillation temperature is room temperature.

[0081] As one of the preferred embodiments, before immersing the zinc-based material in the mixture of the transition metal salt solution and the organic ligand solution, the zinc-based material is pretreated, and the pretreatment process is: polishing and cleaning the surface of the zinc-based material and then immersing it in an etching solution for etching;

[0082] The etching solution includes a mixed solution of sodium hydroxide and ammonium persulfate.

[0083] As one of the preferred embodiments, the zinc-based material is first immersed in the organic ligand solution, oscillated at room temperature for 1 to 5 hours, and then the transition metal salt solution is dripped into the organic ligand solution, oscillated at room temperature for 12 to 48 hours, washed and then dried at 60 to 90° C. to obtain the composite zinc negative electrode material.

[0084] As one of the preferred embodiments, the method for preparing the composite zinc negative electrode material comprises the following steps:

[0085] S1. Grind and clean the surface of the zinc-based material;

[0086] S2, immersing the cleaned zinc substrate in an etching solution for etching;

[0087] S3. Pour the salt solution and the ligand solution into the cleaned zinc-based material in sequence and immerse them, shake at room temperature, wash and dry to obtain the composite zinc negative electrode material.

[0088] An application of a heteronuclear composite zinc negative electrode material based on an in-situ constructed zeolite imidazolate framework in the field of electrochemical energy storage devices, characterized in that the electrochemical energy storage device comprises a zinc ion battery, a zinc-air battery or a zinc-iodine battery.

[0089] Example 1

[0090] This embodiment provides a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework and a preparation method thereof, wherein the preparation process is as follows:

[0091] (1) Cut to 3.5*5cm -2 Use sandpaper to sand both sides until smooth and tape one side with kapton tape.

[0092] (2) Weigh 2g of sodium hydroxide and dissolve it in 10ml of deionized water, stir for 1h, then weigh 0.456g of ammonium persulfate and dissolve it in 10ml of deionized water, stir for 1h. Mix the two solutions, then put the treated zinc foil into the solution and etch for 20min (the mass ratio of sodium hydroxide to ammonium persulfate is 4.4:1). Finally, rinse the etched zinc foil with deionized water three times.

[0093] (3) 0.0104 g of zinc nitrate hexahydrate and 0.0012 g of nickel nitrate hexahydrate were dissolved in 10 ml of deionized water and stirred for 1 h to form a transition metal salt solution. Then 0.256 g of 2-methylimidazole was weighed and dissolved in 15 ml of deionized water and stirred for 1 h to form an organic ligand solution (the molar ratio of the sum of zinc nitrate and nickel nitrate to 2-methylimidazole was 1:8).

[0094] (4) The etched zinc foil was placed in an organic ligand solution and oscillated on a cyclotron at a speed of 90 r / min for 2 h.

[0095] (5) The transition metal salt solution was slowly dripped into the organic ligand solution using a dropper, and then oscillated at 90 r / min at room temperature for 24 h in a cyclotron oscillator, rinsed three times with deionized water, and baked in an oven at 80 °C for 10 min to obtain a composite zinc negative electrode material, named ZIF-L(Ni)@Zn.

[0096] The composite zinc negative electrode material obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0097] The composite zinc negative electrode material obtained above was assembled into a zinc ion full battery with a manganese dioxide positive electrode, and electrochemical tests were carried out using zinc sulfate and manganese sulfate solutions as electrolytes.

[0098] Example 2

[0099] This embodiment provides a heteronuclear trimetallic composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework and a preparation method thereof, wherein the preparation process is as follows:

[0100] (1) Cut to 3.5*5cm -2 Use sandpaper to sand both sides until smooth and tape one side with kapton tape.

[0101] (2) Weigh 2g of sodium hydroxide and dissolve it in 10ml of deionized water, stir for 1h, then weigh 0.456g of ammonium persulfate and dissolve it in 10ml of deionized water, stir for 1h. Mix the two solutions, then put the treated zinc foil into the solution and etch for 20min (the mass ratio of sodium hydroxide to ammonium persulfate is 4.4:1). Finally, rinse the etched zinc foil with deionized water three times.

[0102] (3) 0.0685 g of zinc acetate dihydrate, 0.00956 g of manganese acetate tetrahydrate and 0.00971 g of cobalt acetate tetrahydrate were dissolved in 10 ml of deionized water and stirred for 1 h to form a transition metal salt solution. Then 0.3202 g of 2-methylimidazole was weighed and dissolved in 15 ml of deionized water and stirred for 1 h to form an organic ligand solution (the molar ratio of the sum of zinc acetate, manganese acetate and cobalt acetate to 2-methylimidazole was 1:10).

[0103] (4) The etched zinc foil was placed in an organic ligand solution and oscillated on a cyclotron at a speed of 90 r / min for 2 h.

[0104] (5) The transition metal salt solution was slowly dripped into the organic ligand solution using a dropper, and then oscillated at 90 r / min at room temperature for 24 h in a cyclotron oscillator, rinsed three times with deionized water, and baked in an oven at 80 °C for 10 min to obtain a composite zinc negative electrode material, named ZIF-8(Mn,Co)@Zn.

[0105] The composite zinc negative electrode material obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0106] Comparative Example 1

[0107] This comparative example provides a bare zinc negative electrode material and a preparation method and application thereof, and the preparation process is as follows:

[0108] (1) Cut to 3.5*5cm -2The zinc foil was sanded on both sides until smooth and named Bare Zn.

[0109] The zinc negative electrode obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0110] The zinc negative electrode material obtained above was assembled with a manganese dioxide positive electrode into a zinc ion full battery, and electrochemical tests were carried out using zinc sulfate and manganese sulfate solutions as electrolytes.

[0111] The zinc negative electrode material obtained above and the iodine and activated carbon composite positive electrode were assembled into a zinc-iodine battery, and electrochemical tests were carried out using zinc sulfate solution as the electrolyte.

[0112] Comparative Example 2

[0113] This comparative example provides a mononuclear composite zinc negative electrode material with a non-in-situ constructed zeolite imidazolate framework and a preparation method and application thereof, wherein the preparation process is as follows:

[0114] (1) Dissolve 0.08561 g of zinc acetate dihydrate in 10 ml of deionized water and stir for 1 hour to form a transition metal salt solution. Then weigh 0.3202 g of 2-methylimidazole and dissolve it in 15 ml of deionized water. Stir for 1 hour to form an organic ligand solution. Mix the transition metal solution and the organic ligand solution and stir at room temperature for 24 hours. (The molar ratio of zinc acetate dihydrate to 2-methylimidazole is 1:10).

[0115] (2) The mixed solution was centrifuged at 7000 rpm for 4 min, three times.

[0116] (3) The powder obtained after centrifugation was placed in an oven at 80° C. and dried for 24 h to obtain ZIF-8 powder.

[0117] (4) ZIF-8 powder and polyvinylidene fluoride (PVDF) are mixed and stirred in a molar ratio of (8-20):1 to form a slurry.

[0118] (5) The slurry in (4) was coated on the surface of the zinc foil using a coating apparatus, and then placed in an oven and dried at 80° C. for 24 h to obtain a composite zinc negative electrode material, named ex-situ ZIF-8@Zn.

[0119] The composite zinc negative electrode material obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0120] The zinc negative electrode obtained above and the manganese dioxide positive electrode were assembled into a zinc ion full battery, and electrochemical tests were carried out using zinc sulfate and manganese sulfate solutions as electrolytes.

[0121] Comparative Example 3

[0122] This comparative example provides a heteronuclear composite zinc negative electrode material with a non-in-situ constructed zeolite imidazolate framework and a preparation method and application thereof, wherein the preparation process is as follows:

[0123] (1) 0.0104 g of zinc nitrate hexahydrate and 0.0012 g of nickel nitrate hexahydrate were dissolved in 10 ml of deionized water and stirred for 1 h to form a transition metal salt solution. Then 0.256 g of 2-methylimidazole was weighed and dissolved in 15 ml of deionized water and stirred for 1 h to form an organic ligand solution (the molar ratio of the sum of zinc nitrate and nickel nitrate to 2-methylimidazole was 1:8).

[0124] (2) The mixed solution was centrifuged at 7000 rpm for 4 min, three times.

[0125] (3) The powder obtained after centrifugation was placed in an oven at 80°C and dried for 24 h to obtain ZIF-L(Ni) powder.

[0126] (4) Mix ZIF-L (Ni) powder and polyvinylidene fluoride (PVDF) in a molar ratio of 9:1 to form a slurry.

[0127] (5) The slurry in (4) was coated on the surface of the zinc foil using a coating apparatus, and then placed in an oven and dried at 80° C. for 24 h to obtain a composite zinc negative electrode material, named ex-situ ZIF-L(Ni)@Zn.

[0128] The composite zinc negative electrode material obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0129] The zinc negative electrode obtained above and the manganese dioxide positive electrode were assembled into a zinc ion full battery, and electrochemical tests were carried out using zinc sulfate and manganese sulfate solutions as electrolytes.

[0130] Comparative Example 4

[0131] This comparative example provides a mononuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework and a preparation method and application thereof, wherein the preparation process is as follows:

[0132] 1) Cut 3.5*5cm -2 Use sandpaper to sand both sides until smooth and tape one side with kapton tape.

[0133] (2) Weigh 2g of sodium hydroxide and dissolve it in 10ml of deionized water, stir for 1h, then weigh 0.456g of ammonium persulfate and dissolve it in 10ml of deionized water, stir for 1h. Mix the two solutions, then put the treated zinc foil into the solution and etch for 20min (the mass ratio of sodium hydroxide to ammonium persulfate is 4.4:1). Finally, rinse the etched zinc foil with deionized water three times.

[0134] (3) 0.116 g of zinc nitrate hexahydrate was dissolved in 10 ml of deionized water and stirred for 1 h to form a transition metal salt solution. Then 0.256 g of 2-methylimidazole was weighed and dissolved in 15 ml of deionized water and stirred for 1 h to form an organic ligand solution (the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole was 1:8).

[0135] (4) The etched zinc foil was placed in an organic ligand solution and oscillated on a cyclotron at 90 rpm for 2 h.

[0136] (5) Use a dropper to slowly drip the salt solution into the ligand solution, and then react at room temperature for 24 hours.

[0137] (6) Finally, the obtained in-situ constructed zeolite imidazolate framework composite zinc foil was rinsed three times with deionized water and dried in an oven at 80°C for 10 min to obtain a composite zinc negative electrode material, named ZIF-L@Zn.

[0138] The composite zinc negative electrode material obtained above was assembled into a zinc ion half-cell, and electrochemical testing was carried out using zinc sulfate solution as the electrolyte.

[0139] The zinc negative electrode obtained above and the manganese dioxide positive electrode were assembled into a zinc ion full battery, and electrochemical tests were carried out using zinc sulfate and manganese sulfate solutions as electrolytes.

[0140] Comparative Example 5

[0141] This embodiment provides a mononuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework and a preparation method thereof, wherein the preparation process is as follows:

[0142] (1) Cut to 3.5*5cm -2 Use sandpaper to sand both sides until smooth and tape one side with kapton tape.

[0143] (2) Weigh 2g of sodium hydroxide and dissolve it in 10ml of deionized water, stir for 1h, then weigh 0.456g of ammonium persulfate and dissolve it in 10ml of deionized water, stir for 1h (the mass ratio of sodium hydroxide to ammonium persulfate is 4.4:1). Mix the two solutions, then place the treated zinc foil in the solution and etch for 20min. Finally, rinse the etched zinc foil with deionized water three times.

[0144] (3) Dissolve 0.08561 g of zinc acetate dihydrate in 10 ml of deionized water and stir for 1 hour to form a transition metal salt solution. Then weigh 0.3202 g of 2-methylimidazole and dissolve it in 15 ml of deionized water. Stir for 1 hour to form an organic ligand solution (the molar ratio of zinc acetate dihydrate to 2-methylimidazole is 1:10).

[0145] (4) The etched zinc foil was placed in an organic ligand solution and oscillated on a cyclotron at a speed of 90 r / min for 2 h.

[0146] (5) The transition metal salt solution was slowly dripped into the organic ligand solution using a dropper, and then oscillated at 90 r / min at room temperature for 24 h in a cyclotron oscillator, rinsed three times with deionized water, and baked in an oven at 80 °C for 10 min to obtain a composite zinc negative electrode material, named ZIF-8@Zn.

[0147] The composite zinc negative electrode material obtained above and the zinc iodide and activated carbon composite positive electrode were assembled into a zinc iodine battery, and electrochemical tests were carried out using zinc sulfate solution as the electrolyte.

[0148] Comparative Example 6

[0149] This embodiment provides a mononuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework and a preparation method thereof, wherein the preparation process is as follows:

[0150] (1) Cut to 3.5*5cm -2 Use sandpaper to sand both sides until smooth and tape one side with kapton tape.

[0151] (2) Weigh 2g of sodium hydroxide and dissolve it in 10ml of deionized water, stir for 1h, then weigh 0.456g of ammonium persulfate and dissolve it in 10ml of deionized water, stir for 1h. Mix the two solutions, then put the treated zinc foil into the solution and etch for 20min (the mass ratio of sodium hydroxide to ammonium persulfate is 4.4:1). Finally, rinse the etched zinc foil with deionized water three times.

[0152] (3) 0.08561 g of zinc acetate dihydrate was dissolved in 10 ml of deionized water and stirred for 1 hour to form a transition metal salt solution. Then 0.12808 g of 2-methylimidazole was weighed and dissolved in 15 ml of deionized water and stirred for 1 hour to form an organic ligand solution (the molar ratio of zinc acetate to 2-methylimidazole in zinc acetate dihydrate is 1:4).

[0153] (4) The etched zinc foil was placed in an organic ligand solution and oscillated on a cyclotron at a speed of 90 r / min for 2 h.

[0154] (5) The transition metal salt solution was slowly dripped into the organic ligand solution using a dropper, and then oscillated at 90 r / min at room temperature for 24 h in a cyclotron oscillator, rinsed three times with deionized water, and baked in an oven at 80 °C for 10 min to obtain a composite zinc negative electrode material, named ZIF-7@Zn.

[0155] The composite zinc negative electrode material obtained above and the zinc iodide and activated carbon composite positive electrode were assembled into a zinc iodine battery, and electrochemical tests were carried out using zinc sulfate solution as the electrolyte.

[0156] The surface SEM image of ZIF-L@Zn prepared in Example 1 is as follows Figure 1 ,Depend on Figure 1 It can be seen that ZIF-L grows densely on the surface of zinc foil. The cross-sectional SEM of ZIF-L@Zn is shown in Figure 2. Figure 2 As shown by Figure 2 It can be seen that the thickness of ZIF-L is about 7 μm.

[0157] The surface SEM image of ex-situ ZIF-8@Zn prepared in Comparative Example 2 is shown in Figure 3 ,Depend on Figure 3 It can be seen that ZIF-8 is densely coated on the surface of zinc foil. Figure 4 As shown by Figure 4 It can be seen that the thickness of ZIF-8 is about 12 μm.

[0158] The surface SEM image of ZIF-8@Zn prepared in Comparative Example 5 is as follows Figure 5 ,Depend on Figure 5 It can be seen that ZIF-8 grows densely on the surface of zinc foil. The cross-sectional SEM of ZIF-8@Zn is shown in Figure 2. Figure 6 As shown by Figure 6 It can be seen that the thickness of ZIF-8 is about 12 μm.

[0159] Figure 7 The contact angles of ZIF-L(Ni)@Zn, ex-situ ZIF-L(Ni)@Zn and bare zinc negative electrode materials obtained in Example 1 and Comparative Example 3 are shown in the figure. Among them, Comparative Example 1 obtains a large contact angle of 87° for the bare zinc negative electrode material within 30 seconds, indicating that it has poor wettability with the electrolyte. The contact angle of ex-situ ZIF-L(Ni)@Zn in Comparative Example 3 changes from 55° to 40° within 30 seconds. The contact angle of heteronuclear bimetallic ZIF-L(Ni)@Zn obtained in Example 1 changes from 38° to 20° within 30 seconds, which indicates that the in-situ interface layer can penetrate into the matrix during the formation process, thereby enhancing the mechanical bite of the interface and improving the interface bonding strength. This bonding method is more solid than non-in-situ physical coating, can more effectively transfer stress, and reduce stress concentration and crack formation at the interface. At the same time, the in-situ interface layer can alleviate the difference in elastic modulus between the coating and the substrate, reduce the bending and deformation of the coating during the stress process, thereby improving the overall mechanical properties of the coating.

[0160] Figure 8The ZIF-L(Ni)@Zn prepared in Example 1 and the non-in-situ heteronuclear ZIF-L(Ni)@Zn prepared in Comparative Example 3 were used as zinc ion half-cells at 1 mA cm -2 ,1mAh cm -2 Comparison of cycle stability under current density, where the horizontal axis is time (h) and the vertical axis is voltage (V), the results show that the ZIF-L(Ni)@Zn prepared in Example 1 has better cycle stability than the non-in-situ heteronuclear ZIF-L(Ni)@Zn prepared in Comparative Example 3. This shows that in-situ growth reduces the high energy loss caused by ion diffusion, desolvation shell, and electrodeposition nucleation, inhibits zinc dendrite growth, and improves the compatibility and mechanical stability of the multiphase interface compared to non-in-situ coating.

[0161] Fig. 9 The ZIF-8@Zn prepared in Comparative Example 4 and the bare zinc negative electrode material prepared in Comparative Example 1 were assembled into a zinc-iodine battery at 1Ag -1 Comparison of cycle stability under current density, where the horizontal axis is the number of cycles and the vertical axis is the capacity in grams (mAh g -1 ),Depend on Figure 8 It can be seen that the zinc-iodine battery composed of ZIF-8@Zn prepared in Comparative Example 1 has better cycle stability than the bare zinc negative electrode material.

[0162] Fig.10 The ZIF-8@Zn prepared in Comparative Example 4 and the ex-situ ZIF-8@Zn prepared in Comparative Example 2 were assembled into a zinc ion half-cell at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under current density, where the horizontal axis is time (h) and the vertical axis is voltage (V), Fig. 9 It can be seen that the zinc-zinc symmetric battery composed of ZIF-8@Zn prepared in Comparative Example 4 has better cycle stability than ex-situZIF-8@Zn.

[0163] Fig.11 The ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 were used as zinc ion half-cells at 1 mA cm -2 Comparison of cycling stability under current density, where the horizontal axis is time (h) and the vertical axis is voltage (V), Fig.10 It can be seen that the zinc ion half-cell composed of ZIF-7@Zn has better cycle stability than the bare zinc anode. This shows that the composite zinc anode material significantly promotes the high-flux Zn 2+ transport, ensuring uniform Zn deposition and highly reversible Zn deposition / stripping behavior.

[0164] Fig.12The ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 were used as zinc ion full batteries at different current densities (0.5, 1.0, 2.0, 3.0, 4.0, 0.5 A g -1 ) under different rate performances, where the horizontal axis is the number of cycles and the vertical axis is the capacity in grams (mAh g -1 ),Depend on Fig.11 It can be seen that the zinc ion full battery composed of composite zinc negative electrode material has better rate performance than the bare zinc negative electrode.

[0165] Fig.13 The ZIF-7@Zn prepared in Comparative Example 6 and the bare zinc negative electrode material prepared in Comparative Example 1 were used as zinc ion full batteries at 1A g -1 Comparison of cycle stability under current density, where the horizontal axis is the number of cycles and the vertical axis is the capacity in grams (mAhg -1 ), the results showed that the composite zinc negative electrode material has higher capacity and cycle stability than the bare zinc negative electrode material.

[0166] Fig.14 The heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 respectively form zinc ion half-cells at 1 mA cm -2 ,1mAh cm -2 Comparison of cycling stability under current density, where the horizontal axis is time (h) and the vertical axis is voltage (V), Fig.13 It can be seen that the zinc ion half-cell composed of heteronuclear bimetallic ZIF-L(Ni)@Zn has better cycling stability than that of single-core ZIF-L@Zn. This indicates that the heteronuclear bimetallic ZIF-L(Ni)@Zn significantly promotes the high-flux Zn 2+ transport, ensuring uniform Zn deposition and highly reversible Zn deposition / stripping behavior.

[0167] Fig.15 The heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 were used as negative electrode materials for zinc ion full batteries at different current densities (0.5, 1.0, 2.0, 3.0, 4.0, 0.5 A g -1 ) under different rate performances, where the horizontal axis is the number of cycles and the vertical axis is the capacity in grams (mAh g -1 ),Depend on Fig.14 It can be seen that the zinc ion full battery composed of ZIF-L(Ni)@Zn of Example 1 has better rate performance than the ZIF-L@Zn of Comparative Example 3.

[0168] Fig.16The heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 and the mononuclear ZIF-L@Zn prepared in Comparative Example 4 were used as zinc ion full batteries at 1A g -1 Comparison of cycle stability under current density, where the horizontal axis is the number of cycles and the vertical axis is the capacity in grams (mAh g -1 ), the results show that the heteronuclear bimetallic ZIF-L(Ni)@Zn prepared in Example 1 has higher capacity and cycle stability than the mononuclear ZIF-L@Zn prepared in Comparative Example 4. This shows that the simultaneous introduction of heterometallic centers can further reduce the transport energy barrier of metal ions, while satisfying high electronic and ionic conductivity, and achieving efficient synergistic transfer.

[0169] Fig.17 The heteronuclear trimetallic ZIF-8(Mn,Co)@Zn prepared in Example 2 and the in-situ mononuclear ZIF-8@Zn prepared in Comparative Example 5 were used as zinc ion half-cells at 1 mA cm -2 ,1mAh cm -2 Comparison of cycle stability under current density, where the abscissa is time (h) and the ordinate is voltage (V), the results show that the ZIF-8 (Mn, Co) @ Zn containing the heteronuclear trimetallic prepared in Example 2 has better cycle stability than the in-situ mononuclear ZIF-8 @ Zn prepared in Comparative Example 5. This shows that the simultaneous introduction of multiple heterometallic centers can further reduce the transmission energy barrier of metal ions, while satisfying high electronic and ionic conductivity, and achieving efficient synergistic transfer. The composite zinc negative electrode material based on the in-situ construction of the zeolite imidazolate skeleton prepared by the present invention has good interface compatibility and electrochemical stability, thereby realizing a highly stable zinc metal negative electrode; and the zeolite imidazolate skeleton has abundant nanochannels, which accelerates the desolvation of zinc ions through confinement, realizes uniform transmission of zinc ions, and regulates the deposition kinetics of zinc ions, thereby significantly improving the electrochemical performance of zinc-based batteries.

[0170] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A heteronuclear composite zinc negative electrode material based on an in-situ constructed zeolite imidazolate framework, characterized in that: The composite zinc negative electrode material uses a zinc-based material as a carrier, and an in-situ zeolite imidazolate skeleton interface layer centered on a variety of different transition metals is constructed on the surface.

2. The heteronuclear composite zinc negative electrode material based on in-situ constructed zeolite imidazolate framework according to claim 1, characterized in that: The zeolite imidazolate skeleton interface layer is formed by interconnecting a plurality of different transition metals and organic ligands through self-assembly, wherein the transition metal is the center and the organic ligands are linked to the transition metal. The zeolite imidazolate skeleton interface layer is a crystalline porous material.

3. The heteronuclear composite zinc negative electrode material based on in-situ construction of zeolite imidazolate framework according to claim 2, characterized in that: The transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium; The organic ligands include 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, and 2-bromobenzimidazole; The zinc-based material comprises a zinc foil substrate.

4. A method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to any one of claims 1 to 3, characterized in that: The zinc-based material is immersed in a mixture of a transition metal salt solution and an organic ligand solution, and after shaking, washing and drying, the composite zinc negative electrode material is obtained.

5. The method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to claim 4, characterized in that: The zinc-based material includes a zinc foil substrate; The transition metal salt in the transition metal salt solution includes nitrate, acetate or chloride of a transition metal, the transition metal includes two or more of zinc, iron, manganese, cobalt, nickel, copper and chromium, and the solvent includes one or more of water, methanol, ethanol and dimethylformamide; The organic ligand of the organic ligand solution includes 1-methylimidazole, 1-imidazolecarbonitrile, 2-methylimidazole, 2-ethylimidazole, 2-imidazolidinone, 4,5-dichloroimidazole, benzimidazole, N-methylbenzimidazole, 2-bromobenzimidazole, and the solvent includes one or more of water, methanol, ethanol, and dimethylformamide.

6. The method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to claim 4, characterized in that: The molar ratio of the transition metal salt to the organic ligand is 1:2 to 10; The mass concentration of the transition metal salt is 5 to 15 mg / mL; The mass concentration of the organic ligand is 4-30 mg / mL.

7. The method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to claim 4, characterized in that: The shaking temperature is room temperature.

8. The method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to claim 4, characterized in that: Before immersing the zinc-based material in a mixture of a transition metal salt solution and an organic ligand solution, the zinc-based material is pretreated, wherein the pretreatment process comprises: polishing and cleaning the surface of the zinc-based material and then immersing the surface of the zinc-based material in an etching solution for etching; The etching solution includes a mixed solution of sodium hydroxide and ammonium persulfate.

9. The method for preparing a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework according to claim 4, characterized in that: The zinc-based material is first immersed in the organic ligand solution and oscillated at room temperature for 1 to 5 hours, then a transition metal salt solution is dripped into the organic ligand solution and oscillated at room temperature for 12 to 48 hours, washed and then dried at 60 to 90° C. to obtain the composite zinc negative electrode material.

10. The use of a heteronuclear composite zinc negative electrode material based on in-situ construction of a zeolite imidazolate framework in the field of electrochemical energy storage devices as claimed in any one of claims 1 to 3, characterized in that: The electrochemical energy storage device includes a zinc ion battery, a zinc air battery or a zinc iodine battery.

Citation Information

Patent Citations

  • Zinc ion battery negative electrode material modulated by in-situ growth metal-organic framework and preparation method of zinc ion battery negative electrode material

    CN117691035A